Analisis Kualitas Pelayanan Kesehatan di Unit Pelaksana Teknis Pusat Kesehatan Masyarakat Tarogong Kabupaten Garut - Muchtar Muchtar; Yudi Triana Wahyudi; Kusdinar Kusdinar (Jurnal Pembangunan dan Kebijakan Publik, 2020)
This research aims to determine the quality of health services at Tarogong Public Health Center, Garut Regency along with the factors that inhibit it. The research used qualitative methods with descriptive analysis. Data collection techniques used include observation, interviews, and documentation. Data analysis techniques used are data reduction techniques, data presentation, and conclusion drawing. The results of the research concluded that the quality of health services at Tarogong Public Health Center did not satisfy the users of service for outpatients, inpatients or patient waiters. This can be seen from various indicators of service quality measurement where only the assurance indicator is concluded that employee knowledge is good as well as health employees can provide appropriate services. While the tangible evidence indicators, infrastructure or health service facilities are still inadequate, In the indicator of reliability, services at the Tarogong Pubic Health Center are in accordance with standard operating procedures but the public is still not well informed about the required service requirements, On the indicator of responsiveness (responsiveness), the responsiveness of officers to patient complaints is quite good, whereas in the indicator of empathy (empathy), concern is not yet found in all employees of the Tarogong Public Health Center. The existence of several inhibiting factors that researchers found in the field include: Lack of health care facilities, people do not know the stages of health service procedures, health care workers are not quick to follow up on information provided to patients, there is still a low sense of responsibility for work tasks.The suggestions that can be put forward: propose reimbursement and addition of supporting infrastructure for health services, socialize to the public the operational standards of service procedures, improve employee attitudes and behavior. The role of the leader must be increased again to provide motivation to his subordinates to keep working professionally. Tarogong Public Health Center staff must provide examples to always interact with patients.